2011
DOI: 10.1002/jemt.20991
|View full text |Cite
|
Sign up to set email alerts
|

Lobe variation effects of experimental diabetes and insulin replacement on rat prostate

Abstract: We investigated the impact of diabetes with simultaneous and late insulin replacement on rat prostate growth during puberty, paying special attention to different prostatic lobes. Diabetes was induced by administration of streptozotocin (STZ) in 40-day-old male Wistar rats. A subset of diabetic rats underwent simultaneous insulin replacement (3 days after STZ administration), and another subset underwent a late insulin replacement (20 days after STZ administration). The ventral, dorsolateral, and anterior pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…Ikeda et al indicated that DM caused a substantial reduction in prostatic weight and serum testosterone levels in rats [ 17 ]. Similar results were also reported by Porto et al [ 18 ]. The prostate weight was substantially increased in the BPH control, compared with the normal control.…”
Section: Discussionsupporting
confidence: 92%
“…Ikeda et al indicated that DM caused a substantial reduction in prostatic weight and serum testosterone levels in rats [ 17 ]. Similar results were also reported by Porto et al [ 18 ]. The prostate weight was substantially increased in the BPH control, compared with the normal control.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to corroborate with previous evidence that diabetes markedly reduces cell proliferation and increases apoptosis in the prostate [ 37 , 39 , 43 , 53 ], the present results indicate, for the first time, that MLT administration (10 μ g/kg body weight/day) to Wistar rats retrieved the proliferative activity of the prostate after two months of experimental diabetes. This retrieval was associated with improvement of the androgen synthesis that is known to be impaired in chronic diabetes [ 43 , 45 , 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies report that induction of diabetes caused a significant reduction in serum testosterone levels and in prostatic weight in rats (19,54). The lobe response to diabetes varied (92). After 1 wk, diabetes led to an atrophy of~35% in the ventral prostate and an increase in collagen (41).…”
Section: T1dm and Ucodmentioning
confidence: 99%